The Effect of Black Cumin (Nigella sativa) on Histopathology of Liver and Kidney in Albino Rats with Organophosphate Exposure - Hendrawan, Viski Fitri; Oktanella, Yudit; Firmawati, Aulia; Agustina, Galuh Chandra (Universitas Airlangga, 2023)
This study aimed to determine the effect of black cumin extract (Nigella sativa) on the histopathological of the liver and kidneys in albino rats exposed to organophosphates. This study used 20 male mice divided into five treatment groups, i.e. (K-) without organophosphate and black cumin, (K+) induced by organophosphate 40 mg/kg BW, treatment group induced by organophosphate 40 mg/kg BW and black cumin extract as therapy (P1 ) 200 mg/kg BW, (P2) 400 mg/kg BW, and (P3) 600 mg/kg BW. Organophosphate administration for eight weeks and black seed extract therapy was given for three weeks then the mice were euthanized, the liver and kidney organs were taken for histopathological observation using Haematoxylin-Eosin (HE). Data were analyzed using OneWay ANOVA test followed by Tukey test. The results showed that there were significant differences between the treatment groups for liver and kidney damage (p<0,05). Hepatic degeneration and necrosis in the P2 and P3 groups differed from K+ with an average of 2,24±0,9, in the kidneys with an average of 2,52±0,8. It can be concluded that black cumin extract has a significant effect on improving the liver and kidneys in groups P3 (600 mg/kgBW).